Validation of the MoCA versus MMSE against hypertension and hypertensive arteriopathy after TIA or minor stroke - Webb, Alastair JS (Stroke, 2014)
BACKGROUND AND PURPOSE: Lack of reduced cognitive impairment with blood pressure (BP) lowering in trials may reflect use of the Mini-Mental State Examination (MMSE), which is insensitive to mild cognitive impairment after cerebrovascular events compared to the Montreal Cognitive Assessment (MOCA). We determined relationships between impairment on MMSE vs. MoCA with the major physiological determinant of vascular cognitive impairment: hypertension and hypertensive arteriopathy. METHODS: Cognitive impairment in consecutive patients 6 months after TIA or minor stroke was defined as “significant”, “mild” or “none” (MMSE<23,23-26,≥27; MOCA<20,20-24,≥25) and related to 20 premorbid systolic blood pressure (SBP) readings, home BP (HBPM, 3 measurements, 3 times daily for one month) and hypertensive arteriopathy (creatinine, stroke vs TIA, leukoaraiosis), by ordinal regression. RESULTS: Of 463 patients, 45% vs 28% had at least mild cognitive impairment on the MOCA vs MMSE (p<0.001). Hypertensive arteriopathy was more strongly associated with cognitive impairment on the MOCA than MMSE (Creatinine:OR=3.99, 95%CI 2.06-7.73 vs 2.16, 1.08-4.33; event:1.53, 1.06-2.19 vs 1.23, 0.81-1.85; leukoaraiosis:2.09, 1.42-3.06 vs 1.34, 0.87-2.07). Premorbid and HBPM SBP were more strongly associated with impairment on vascular subdomains of the MoCA than MMSE (OR/10mmHg: visuo-spatial 1.29 vs 1.05; attention 1.18 vs 1.07; language 1.22 vs 0.91; naming 1.07 vs 0.86). CONCLUSIONS: The stronger relationship between impairment on the MoCA with hypertensive arteriopathy, independent of age, indicates a greater sensitivity for vascular-origin cognitive impairment. Use of MoCA should improve sensitivity for cognitive impairment and treatment effects in future studies.